DAYADUKUNG TANAH UNTUK BERBAGAI TIPE FONDASI TAPAK PADA LEMPUNG PLASTISITAS TINGGI DI BEBERAPA LOKASI, KABUPATEN MAJALENGKA, JAWA BARAT - -, Zufialdi Zakaria; -, Agung Mulyo; -, Luthfan H. Jihadi; -, M. Bey Anural (Bulletin of Scientific Contribution, 2013)
The research location at Majalengka and its surrounding, West Java. The study was conducted in an effort to know soil bearing capacity for various types of foundations which depend on the physical and material properties of the soil. Location of samples obtained from three locations: Kertajati, Cikijing and Cigintung. Samples obtained in the form of high plasticity clay (CH) with the activity rate (A) between 1.01 to 1.42 (with Skempton method) or 1.12 to 1.61 (the Seed method), samples are high activity clays, included of monmorilonitic mineral. Alloweble soil bearing capacity (qa) for a square foundation type, between 11.04 to 19.50 T/M2; for a circular (rounded) foundation types, from 11.00 until 19.07 T/M2; and for the type of continuous foundation, between 8 , 85 to 15.28 T/M2. To avoid of the failure of the foundation, the building load should not exceed the value of allowable soil bearing capacity. The estimated expansive soils, soil improvement is required to be done.